ANALISIS PENDEKATAN STRUKTURAL (UNSUR INTRINSIK) PADA NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOH - Redia Renata Simanjuntak (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the structure of the novel Ronggeng Dukuh Paruk by Ahmad Tohari through a structural approach with a focus on intrinsic elements. The method used is descriptive qualitative with content analysis techniques. The results of the study indicate that the intrinsic elements in the novel are interrelated and form a comprehensive meaning. The storyline follows a linear pattern with several flashbacks, the main character has significant character development, the setting of place and time are crucial supporting elements for the main theme, and the language style is rich in local Javanese vocabulary and symbolism. The main themes that emerge are the struggle for life, cultural identity, and the social dynamics of rural communities during the transition period. This study provides a deeper understanding of the structural construction of the novel that has become a classic work of Indonesian literature.